Combined effects of steel fiber and strain rate on the biaxial compressive behavior of concrete. (30th October 2018) - Bao, Jiuwen; Wang, Licheng; Zhang, Qiuyu; Liang, Yongqin; Jiang, Peiqing; Song, Yupu
Highlights: Dynamic biaxial compressive experiments on SFRC were conducted. Combined effects of strain rate and steel fiber on dynamic strength were analyzed. Dynamic strength criterion of SFRC considering stress ratio was proposed. Model results well agreed with experiments at strain rates from 10 −5 /s to 10 −2 /s. Abstract: Understanding the biaxial mechanical behavior of steel fiber reinforced concrete (SFRC) is of critical significance when the concrete structures are subjected to dynamic loading. This paper presents the results of an experimental investigation on the dynamic mechanical behavior of SFRC subjected to biaxial compressive loadings. Aiming at the combined effects of steel fiber and strain rate on strength criterion, a series of dynamic biaxial compressive experiments on 100 mm-length SFRC cubic specimens with various steel fiber contents (0%, 1%, 2%, and 3% by volume) were conducted by using a large dynamic triaxial servo-hydraulic testing apparatus. The specimens were loaded by biaxial compression with five stress ratios (i.e. 0:1, 0.25:1, 0.5:1, 0.75:1 and 1:1, respectively) at various strain rates ranging from 10 −5 /s to 10 −2 /s. A comprehensive dynamic biaxial strength criterion taking into account the combined effects of uniaxial strength, strain rate and stress ratio was proposed. The effect of steel fiber content and strain rate on the biaxial mechanical behavior of SFRC specimens was discussed, including the failure mode, stress-strain curve, biaxial compressive strength, dynamic strength criterion. It suggested that at given strain rate, the biaxial stress ratio is the major factor dominating the strength increment, and the incorporation of steel fiber has a remarkable enhancement on the strength for all stress ratios. Additionally, the dynamic compressive strengths of SFRC were found to increase with the increase of strain rate, while the failure pattern and dynamic ultimate strength were closely dependent on the magnitude of lateral stress exerted on the specimens. The comparison indicates that the proposed model results of dynamic strength criterion were in good agreement with the experimental data for SFRC specimens.